2006
DOI: 10.1364/ol.31.002338
|View full text |Cite
|
Sign up to set email alerts
|

Observation of staggered surface solitary waves in one-dimensional waveguide arrays

Abstract: The observation of nonlinear staggered surface states at the interface between a substrate and a one-dimensional self-defocusing nonlinear waveguide array is reported. Launching of staggered input beams of different power in the first channel of the array results in formation of localized structures in different channels. Our experimental results are confirmed numerically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 20 publications
8
69
0
2
Order By: Relevance
“…These surface solitons can be understood as discrete optical solitons localized near the surface provided their power exceeds a certain threshold value, compensating the repulsive action of the surface [4]. A similar effect of the light localization near the edge of the waveguide array and the formation of surface gap solitons have been predicted and observed for defocusing nonlinear periodic media [2,5,6,7].…”
Section: Introductionsupporting
confidence: 55%
“…These surface solitons can be understood as discrete optical solitons localized near the surface provided their power exceeds a certain threshold value, compensating the repulsive action of the surface [4]. A similar effect of the light localization near the edge of the waveguide array and the formation of surface gap solitons have been predicted and observed for defocusing nonlinear periodic media [2,5,6,7].…”
Section: Introductionsupporting
confidence: 55%
“…These surface solitons become possible solely due to discreteness effects and they exist in neither continuous nor linear limits. Some of the specific features of such discrete surface optical solitons in other relevant physical settings have been recently investigated both theoretically [20][21][22][23][24][25][26][27] and experimentally [28][29][30][31] (see also Ref. [32][33][34] for recent comprehensive overviews of experimental and theoretical developments in the area of discrete optical solitons).…”
Section: Introductionmentioning
confidence: 99%
“…In these two papers it has been revealed that the vicinity of the edge enables a stable propagation of various localized modes, such as flat-top modes and inter-site ones (mode B) [23]. Very recently, strongly localized surface waves have been independently observed in NWA exhibiting saturable [24,25] and quadratic nonlinearity [26], respectively. The fact that a surface can support the existence of localized states has been, for example, further exploited in vector [27], nonlocal [28] as well as binary NWA [29], and in a soliton array case [30].…”
mentioning
confidence: 99%
“…Please note that, from the surface's point of view, Tamm oscillations do not belong to nonlinear effects (i.e. they exist for light intensities lower than the threshold for the onset of highly nonlinear Tamm states [9,20,21,22,24,25,26]). …”
mentioning
confidence: 99%